Mechanical Properties and Structural Behavior of Sustainable Ferrock Concrete for Green Construction Applications - Elbialy, Samy; Alhoutary, I.; Gouda, Ahmed; Ibrahim, Amr M. N.; Ibrahim, Wael; Ibrahim, Amal Hassanin; Abd-Allah, Waleed (Civil Engineering Journal, 2026)
This study aims to develop a sustainable alternative to Ordinary Portland Cement (OPC) by investigating the mechanical and structural properties of Ferrock concrete, an iron carbonate-based binder composed largely of industrial by-products. An experimental program was conducted, testing over 114 concrete cubes, 18 cylinders, and 6 full-scale reinforced concrete beams with Ferrock replacing OPC at 5%, 10%, 15%, 20%, and 25% by weight. The results demonstrate that a 15% replacement ratio yields a 25% increase in 28-day compressive strength, while splitting tensile strength improves consistently with Ferrock content. Most notably, reinforced beams with 20% Ferrock exhibited up to a 33% increase in flexural capacity, with failure modes shifting toward more ductile behavior and experimental capacities exceeding predictions from ACI 318, CSA A23.3, and Eurocode 2 by up to 62%. This research confirms that Ferrock is not only a carbon-negative material but also a technically superior partial replacement for OPC, offering enhanced strength, ductility, and structural performance for green construction applications.